2010
DOI: 10.2136/sssaj2009.0313
|View full text |Cite
|
Sign up to set email alerts
|

Cutin and Cutan Biopolymers: Their Role as Natural Sorbents

Abstract: The aliphatic biopolymers cutin and cutan are important precursors of soil organic matter. In this study, we examined the effects of these biopolymers' decomposition and transformation in the soil on their sorptive properties. The levels of cutin and cutan decreased by 35 and 30%, respectively, after 20 mo of incubation. Carbon‐13 nuclear magnetic resonance and differential scanning calorimeter analyses suggested that the rigid (crystalline) polymethylene moieties of cutan decompose with time. This observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Environmental perturbations also lead to changes in the chain‐length distributions in waxes (Shepherd & Griffiths, ), which is evident in plants adapted to warmer and drier climates, such as the Mediterranean, with these plants showing a greater proportion of longer chain (C34‐C37) alkanes in their waxes than plants adapted to cooler and wetter climates (Dodd & Poveda, ). Because of the depolymerization susceptibility of the ester linkages in cutin, this polymer is labile, whereas cutan and crystalline waxes are more recalcitrant and hydrophobic (Boom et al., ; Shechter, Xing, & Chefetz, ; Stimler, Xing, & Chefetz, ). Thus, along with the quantitative increase in cuticular matrices, the acclimation by plants to stressful climates could be caused by increases in cutan and crystalline waxes in the cuticle.…”
Section: Effect Of Climatic Stress On the Chemical Composition Of Plamentioning
confidence: 99%
“…Environmental perturbations also lead to changes in the chain‐length distributions in waxes (Shepherd & Griffiths, ), which is evident in plants adapted to warmer and drier climates, such as the Mediterranean, with these plants showing a greater proportion of longer chain (C34‐C37) alkanes in their waxes than plants adapted to cooler and wetter climates (Dodd & Poveda, ). Because of the depolymerization susceptibility of the ester linkages in cutin, this polymer is labile, whereas cutan and crystalline waxes are more recalcitrant and hydrophobic (Boom et al., ; Shechter, Xing, & Chefetz, ; Stimler, Xing, & Chefetz, ). Thus, along with the quantitative increase in cuticular matrices, the acclimation by plants to stressful climates could be caused by increases in cutan and crystalline waxes in the cuticle.…”
Section: Effect Of Climatic Stress On the Chemical Composition Of Plamentioning
confidence: 99%
“…In intact cuticle or in soils amended with cuticle that have been incubated for shorter periods of time (i.e., <24 mo), the OC is probably less tightly attached to the mineral matrix, and fewer condensed and rigid domains are available for phenanthrene sorption. This would explain the more linear isotherms observed in previous studies (Chefetz, 2007; Shechter et al, 2010; Stimler et al, 2006).…”
Section: Resultsmentioning
confidence: 53%
“…Because cutin is an amorphous polyester, its biodegradation is expected to be facilitated as compared with the polyethylene‐like biopolymer cutan (Kögel‐Knabner, 2002). Shechter et al (2010) reported an overall 30% degradation of cutin and cutan incubated for 20 mo with sandy loam soil. In the current study, cuticle degradation of tomato and agave cuticles was much higher (67 and 73%, respectively) for the loamy sand soil, probably due to the presence of more labile OC in the whole cuticle as compared with the isolated biopolymers used by Shechter et al (2010).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations